2020
DOI: 10.3390/rs12213652
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty and Overfitting in Fluvial Landform Classification Using Laser Scanned Data and Machine Learning: A Comparison of Pixel and Object-Based Approaches

Abstract: Floodplains are valuable scenes of water management and nature conservation. A better understanding of their geomorphological characteristic helps to understand the main processes involved. We performed a classification of floodplain forms in a naturally developed area in Hungary using a Digital Terrain Model (DTM) of aerial laser scanning. We derived 60 geomorphometric variables from the DTM and prepared a geomorphological map of 265 forms (crevasse channels, point bars, swales, levees). Random Forest classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…For levee detection, found that PC for image segmentation, DEM analysis, and integrated analysis methods was about 30%, 95%, and 80%, and DT was about 45%, 65%, and 50%. Object-oriented and pixel-based classification methods applied by Csatáriné Szabó et al (2020) provided overall accuracies of 75%-80%. The PC and DT found using persistence rank among the highest-performing of the semi-automated methods they tested for levees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For levee detection, found that PC for image segmentation, DEM analysis, and integrated analysis methods was about 30%, 95%, and 80%, and DT was about 45%, 65%, and 50%. Object-oriented and pixel-based classification methods applied by Csatáriné Szabó et al (2020) provided overall accuracies of 75%-80%. The PC and DT found using persistence rank among the highest-performing of the semi-automated methods they tested for levees.…”
Section: Discussionmentioning
confidence: 99%
“…Object‐oriented and pixel‐based classification methods applied by Csatáriné Szabó et al. (2020) provided overall accuracies of 75%–80%. The PC and DT found using persistence rank among the highest‐performing of the semi‐automated methods they tested for levees.…”
Section: Discussionmentioning
confidence: 99%
“…We selected RF not only because it has become a frequently applied machine learning technique in various fields (e.g. [53][54][55][56]), but it commonly outperforms other techniques as well [23,57]. Before fitting RF between the indicators and the environmental covariates listed in Table 3, we fine-tuned the hyper-parameter mtry of RF that is the number of input covariates selected randomly at each split.…”
Section: Spatial Modelling and Classification Of Sasmentioning
confidence: 99%